Transformational Leadership of School Principals in Improving Scouting Achievements at SDN Bringin 01 Semarang City - Arifana Arifana; Bunyamin Bunyamin; Rasiman Rasiman (Dinasti International Journal of Education Management And Social Science, 2025)
This research is titled "Transformational Leadership of School Principals in Improving Scout Achievement at SDN Bringin 01 Semarang City" and aims to analyze how the school principal applies transformational leadership to enhance students' scouting achievements at SDN Bringin 01 Semarang City. The research method used is a qualitative approach, with data collection techniques including observation, interviews, and documentation. The results show that the principal at SDN Bringin 01 Semarang City implements four main dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. In terms of idealized influence, the principal serves as a role model for teachers and students through integrity, commitment, and behavior that reflects scouting values. Inspirational motivation is manifested through clear vision communication and optimistic messaging, which successfully boosts work spirit and active involvement in scouting activities. Intellectual stimulation is applied by encouraging teachers to innovate in teaching methods and the implementation of scouting activities. Meanwhile, individualized consideration is shown by paying special attention to the personal development needs of teachers and students, thereby creating strong interpersonal relationships. Overall, this research concludes that the transformational leadership of the school principal plays a crucial role in creating a collaborative, innovative, and supportive school environment. This positively impacts the improvement of students' scouting achievements at SDN Bringin 01 Semarang City. The findings are expected to contribute to the development of effective leadership models in the context of primary education, particularly in scouting.